Respuesta :
Answer: C.) f(x) = -2x + 5
If you start from x=1, you will see the patter follows -2x + 5
-2(1) +5 = -2+5 = 3
-2(2)+ 5 = -4 + 5 = 1
-2(3) + 5= -6 +5 = -1
And so on...
If you start from x=1, you will see the patter follows -2x + 5
-2(1) +5 = -2+5 = 3
-2(2)+ 5 = -4 + 5 = 1
-2(3) + 5= -6 +5 = -1
And so on...
Answer: Option 'c' is correct.
Step-by-step explanation:
Since we have given that
3, 1, −1, −3, −5, −7, ...
Here, a = 3
d = a₂-a₁=1-3=-2
Let the number of terms be 'x'.
As we know the formula for "Arithmetic sequence":
[tex]f(x)=a+(x-1)d\\\\f(x)=3-2(x-1)\\\\f(x)=3-2x+2\\\\f(x)=-2x+5[/tex]
Hence, Option 'c' is correct.